2011
DOI: 10.1007/s12035-011-8182-4
|View full text |Cite
|
Sign up to set email alerts
|

Bending Tau into Shape: The Emerging Role of Peptidyl-Prolyl Isomerases in Tauopathies

Abstract: The Hsp90-associated cis-trans peptidyl-prolyl isomerase—FK506 binding protein 51 (FKBP51)—was recently found to co-localize with the microtubule (MT)-associated protein tau in neurons and physically interact with tau in brain tissue from humans who died from Alzheimer’s disease (AD). Tau pathologically aggregates in neurons, a process that is closely linked with cognitive deficits in AD. Tau typically functions to stabilize and bundle MTs. Cellular events like calcium influx destabilize MTs, disengaging tau. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…In vitro studies demonstrated that PPIase activity of FKBP51 regulates and balances the phosphorylation state of tau for microtubule stabilization (Jinwal et al 2010;Koren et al 2011). Interestingly, knockdown of FKBP51 dramatically reduced tau levels while inhibiting its PPIase activity led to increased stability and accumulation of phosphorylated tau (Jinwal et al 2010).…”
Section: Fkbp51mentioning
confidence: 99%
“…In vitro studies demonstrated that PPIase activity of FKBP51 regulates and balances the phosphorylation state of tau for microtubule stabilization (Jinwal et al 2010;Koren et al 2011). Interestingly, knockdown of FKBP51 dramatically reduced tau levels while inhibiting its PPIase activity led to increased stability and accumulation of phosphorylated tau (Jinwal et al 2010).…”
Section: Fkbp51mentioning
confidence: 99%
“…Indeed, genetic studies have shown that PPIases are essential to the function/folding of proteins important in cancer, neurodegenerative disorders, viral infection, and psychiatric disorders. 47 …”
Section: Introductionmentioning
confidence: 99%
“…PTMs are also involved in the effect of FKBP51 on microtubule dynamics. It is assumed that phosphorylation of tau leads to its dissociation from microtubules and adoption of the trans configuration of specific peptidylprolyl bonds, while the association of phosphorylated tau with FKBP51 promotes its dephosphorylation and cis configuration that is required for microtubule association [71][72][73].…”
Section: On or Off? Fkbp51 Associates With Both Kinases And Phosphatasesmentioning
confidence: 99%